Analysis of the Application of E-Filing in Efforts to Improve Taxpayer Compliance in Submitting Annual Tax Returns at the Manado Primary Tax Service Office - Rachel Danielle Adriana Aling; Robert Lambey; Sonny Pangerapan (Asian Journal of Applied Business and Management, 2023)
E-filing is a way of submitting Annual Tax Return electronically and in real time through the DJP Online tax e-filing website or applications managed by tax application service providers (ASP). This research was conducted to evaluate the implementation of the e-filing system at KPP Pratama Manado with the aim of improving taxpayer compliance and identifying factors that support and hinder the implementation of e-filing. The research method used is qualitative with a descriptive approach. The results showed that the use of e-filing has a good impact on the level of taxpayer compliance, especially for individual taxpayers. In addition, the results identify the benefits and challenges faced by taxpayers and KPP Pratama Manado in dealing with e-filing.